OPTIMIZATION OF SURFACTANT FLOODING ON BJG FIELD USING DYNAMIC PATTERN - Ajeng Purna Putri Oktaviani; Leksono Mucharam (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2020)
Mature fields, also known as brownfields, are fields that are in a state of declining production or reaching the end of their production lives.  Development of mature oil fields has been, and will increasingly be, an exciting subject (Babadagli, 2007). New studies already discovered innovative ways of finding, developing, and producing hydrocarbons that are efficient and cost-effective and minimize harm to the environment. BJG Field is one of the mature fields which is produced in 1927, one of the efforts for enhancing the production is using waterflood at the beginning of 2001. To increase production further, then we need to conducted studies as an application of the second recovery from BJG Field. The oil recovery factor BJG field can be increased using a surfactant flooding scenario. This research aimed to conduct a study of dynamic pattern surfactant flooding using simulations as applicable for the mature field. The research is expected to obtain an optimum surfactant injection scenario using IMEX and STARS simulator. Simulation is done with real data from the BJG field, and the result has shown the scenario which has the most significant oil production. The highest recovery factor is the chosen scenario. From the results of studies and simulation shown that dynamic pattern inverted five-spot pattern can be used. The increment of oil recovery factor is 32.29% from the waterflood case.